2015
DOI: 10.3390/nu7042485
|View full text |Cite
|
Sign up to set email alerts
|

Meta-Analysis of the Association between Vitamin D and Autoimmune Thyroid Disease

Abstract: Although emerging evidence suggests that low levels of vitamin D may contribute to the development of autoimmune disease, the relationship between vitamin D reduction and autoimmune thyroid disease (AITD), which includes Graves’ disease (GD) and Hashimoto thyroiditis (HT), is still controversial. The aim was to evaluate the association between vitamin D levels and AITD through systematic literature review. We identified all studies that assessed the association between vitamin D and AITD from PubMed, Embase, C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
161
3
10

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 198 publications
(181 citation statements)
references
References 41 publications
7
161
3
10
Order By: Relevance
“…It regulates T helper lymphocytes (Th1, Th2, Th17) and their cytokine secretion (as IFN γ), which are involved in the development of thyroid autoimmunity [15]. A correlation between AIT and reduced vitamin D action (as some polymorphisms of vitamin D receptor gene, vitamin D binding proteins, 1-and 25 hydroxylase) has also been demonstrated [16].…”
Section: Discussionmentioning
confidence: 99%
“…It regulates T helper lymphocytes (Th1, Th2, Th17) and their cytokine secretion (as IFN γ), which are involved in the development of thyroid autoimmunity [15]. A correlation between AIT and reduced vitamin D action (as some polymorphisms of vitamin D receptor gene, vitamin D binding proteins, 1-and 25 hydroxylase) has also been demonstrated [16].…”
Section: Discussionmentioning
confidence: 99%
“…In comparison to healthy controls, subjects with hypothyroidism have significantly lower circulating concentration of 25(OH)D [4]. Animal studies have shown that vitamin D is a basic factor, necessary for normal insulin secretion [5].…”
Section: Introductionmentioning
confidence: 99%
“…Thyroid function test and anti-thyroid antibodies should be analyzed for disease detection. The level of TSH is inversely proportional to the level of T3 and T4 (2)(3)(4). In females, it plays an important role through direct and indirect mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…Vitamin D receptors were detected in bone, kidney, intestine, muscles, brain, liver and immune system (T, B cells, macrophages, monophages). Vitamin D has a potent role in regulating calcium-phosphorus metabolism (4). Vitamin D is considered as an essential immunoregulator.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation